High Compensation Creates a Ratchet Effect - Amihai Glazer; Hans Gersbach (Institute for the Study of Labor (IZA), 2004)
We consider a firm which pays a worker for his effort over several periods. The more the firm pays in one period, the wealthier the worker is in the following periods, and so the more he must be paid for a given effort. This wealth effect can induce an employer to pay little initially and more later on. For related reasons, the worker may work harder than the employer prefers. The incentive contracts firms offer may therefore cap the worker?s earnings. Lastly, this wealth ratchet effect can induce excessive firing and turnover.
Keywords: J60; J30; D80; 330; principal-agent; compensation; moral hazard; wealth effects; Ratchet effects; high-powered incentives; Vergütungssystem; Anreizvertrag; Leistungsmotivation; Vermögenseffekt; Arbeitsmobilität; Agency Theory; Theorie